DEALING WITH DISRUPTIVE STUDENTS IN ELEMENTARY SCHOOL - Akhmatova , Madina Makhmud kizi,; Khasanova, Yulduz Mukhtor kizi, (Innovative Development in Educational Activities, 2024)
The purpose of this research is to determine the causes of disruptive behavior among the first grade pupils. In order to facilitate the effective learning, it is important to clarify misbehavioring in the classroom and avoid it. Conducting research related to this topic, alongside gathering knowledge from other surveys, demonstrates that disruptive behavior may occur when classroom is not arranged properly. The aim of quantitative method in this investigation is to identify the forms and reasons of disruptive behavior among pupils by giving their appropriate percentage. In order to conduct the research one school where located in Navai had been chosen. About 30 pupils who are at the first grade had been interviewed and their teachers were asked to help find the occurrence of disruptive behavior among young learners. Learning process is difficult one. It is commonly argued that if the classroom has a good atmosphere and support of teachers, students tend to learn effectively. Because the existence of disruptive behavior also depends on teachers’ skills. When the teacher gives profitable knowledge to pupils, they desire to study a lot without any disruption.